Plasmonics in Topological Insulators - Yi-Ping Lai; I-Tan Lin; Kuang-Hsiung Wu; Jia-Ming Liu (Nanomaterials and Nanotechnology, 2014)
With strong spin-orbit coupling, topological insulators have an insulating bulk state, characterized by a band gap, and a conducting surface state, characterized by a Dirac cone. Plasmons in topological insulators show high frequency-tunability in the mid-infrared and terahertz spectral regions with transverse spin oscillations, also called “spin-plasmons”. This paper presents a discussion and review of the developments in this field from the fundamental theory of plasmons in bulk, thin-film, and surface-magnetized topological insulators to the techniques of plasmon excitation and future applications.